Implementasi Kurikulum Merdeka Dalam Pembentukan Karakter Siswa SD Al-Madina Wonosobo - Aza Ima Rahmatika; Abdul Majid; Fatiatun (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
In this research, the author aims to investigate the implementation of the Merdeka Curriculum in forming the character of Al-Madinah Elementary School students, Wonosobo. This research uses a qualitative approach with a case study design. Data was collected through classroom observations, interviews with teachers and students, as well as document analysis related to the implementation of the Independent Curriculum. The study findings show that the independent learning curriculum has been implemented at the Al-Madinah Wonosobo Elementary School, but teachers experienced several obstacles in implementing it. Obstacles related to understanding revolve around a lack of understanding of the concept of "freedom to learn", the difficulty of changing old habits such as still using the lecture method. In the context of building student character, the Independent Curriculum can be implemented in various ways, one of which is a holistic approach, integration of national values, and student empowerment. It is recommended that this approach be implemented widely at the elementary school level as part of comprehensive and sustainable character education efforts.